Sistem Pemrosesan Transaksi Pada Toko Bangunan Berbasis Web Dengan PHP dan MySQL - Rizky Gelar Maliq; R. Rizal Isnanto; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2014)
Building supply store is a business entity engaged in the sale of construction materials for the building. Where there are still use the transaction data were administrative in bookkeeping way , so it takes a long time to figure out the sale and purchase transactions. Therefore, the author here takes issue in the sale and purchase itself. Transaction processing systems created using PHP programming language and MySQL database. System where this information can help in recording the transaction in the building supply store . In addition to recording can also be used for the preparation of monthly reports. The expected result from design of this transaction processing systems is to build a computerized information system to facilitate the operator in the transaction. With this expected to improve customer service so well that the presentation of information in a relatively quick and accurate transactions. Moreover, it can accelerate the collection of goods to see inventory and preparing reports.